To what extent does share ownership affect informative earnings management? Evidence from Indonesian manufacturing sector - Mela, Nanda Fito; Putra, Adhitya Agri; Abdurrahman, Rezi; Lubis, Armensyah (JIFA (Journal of Islamic Finance and Accounting), 2023)
Inconsistent findings regarding the relationship between share ownership and earnings management, specifically in terms of informative and opportunistic practices, have been observed in previous studies. To address this gap, the present research aims to investigate the impact of institutional, governmental, and family ownership on informative earnings management. The sample comprises 615 manufacturing firm-year observations listed on the Indonesian Stock Exchange. Earnings management is assessed by examining discretionary accruals, which are further categorized into informative and opportunistic acts based on earnings growth. Logistic regression analysis is employed to analyze the data. The results indicate that both institutional and family ownership have a positive effect on informative earnings management. This suggests that institutional and family shareholders play influential roles in monitoring managerial behavior, particularly in encouraging informative earnings management practices rather than opportunistic ones. Conversely, governmental ownership does not have a significant effect on earnings management. This finding suggests that government shareholders may have lesser interest in evaluating managerial performance based on earnings and instead prioritize political and social considerations. Overall, this study contributes to the existing literature by shedding light on the distinct influences of different types of share ownership on earnings management practices, particularly in terms of their impact on informative earnings management.